2015
DOI: 10.1371/journal.pone.0122163
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and Patterns of Ground-Dwelling Beetle Biodiversity across Northern Canada

Abstract: Many macroecological patterns of biodiversity, including the relationship between latitude and species richness, are well-described. Data collected in a repeatable, standardized manner can advance the discipline beyond the description of patterns and be used to elucidate underlying mechanisms. Using standardized field methods and a hyper-diverse focal taxon, viz. Coleoptera, we aim to (1) describe large-scale latitudinal patterns of taxonomic diversity, functional diversity, and assemblage structure across nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 57 publications
(68 reference statements)
3
18
0
Order By: Relevance
“…We found that climatic factors, and in particular temperature, were the most important variables in predicting the variability in carabid species composition, both at regional scale and for grassland types, except for the desert steppe, for which these factors had limited explanatory power. Temperature has been reported as the most important environmental factor for carabid communities (Eyre et al, 2005;Ernst & Buddle, 2015;Yu et al, 2016), and our results support this conclusion. Previous research found that vegetation and soil characteristics are also important drivers of carabid species composition (Holmes, Boyce & Reed, 1993;Perner & Malt, 2003;Schaffers et al, 2008;Gioria et al, 2010;Birkhofer et al, 2015;Liu et al, 2016;Vogels et al, 2017;Ng, et al, 2018b).…”
Section: Discussionsupporting
confidence: 91%
“…We found that climatic factors, and in particular temperature, were the most important variables in predicting the variability in carabid species composition, both at regional scale and for grassland types, except for the desert steppe, for which these factors had limited explanatory power. Temperature has been reported as the most important environmental factor for carabid communities (Eyre et al, 2005;Ernst & Buddle, 2015;Yu et al, 2016), and our results support this conclusion. Previous research found that vegetation and soil characteristics are also important drivers of carabid species composition (Holmes, Boyce & Reed, 1993;Perner & Malt, 2003;Schaffers et al, 2008;Gioria et al, 2010;Birkhofer et al, 2015;Liu et al, 2016;Vogels et al, 2017;Ng, et al, 2018b).…”
Section: Discussionsupporting
confidence: 91%
“…Given that the Lycosidae egg sac parasitism is surprisingly high in some subarctic populations (Bowden and Buddle 2012), biotic interactions may play a greater role in structuring local diversity in the Arctic than expected. This might be explained by the important biomass of predators compared with herbivores or detritivores in the Arctic (Ernst and Buddle 2015). Experiments on spider parasitism, cannibalism (see Asmus 2017 for example), and competition will help to unravel some of the biotic interactions that have largely been forsaken in the recent literature on Arctic food webs based on molecular data (Roslin et al 2013;Wirta et al 2015).…”
Section: Loboda and Buddlementioning
confidence: 99%
“…Ecological patterns and processes in more temperate regions are known to differ from those in tropical regions (Algar et al 2011), and it is reasonable to assume patterns and processes in Arctic regions, which have received little attention (but see Ernst and Buddle 2015;Hansen et al 2016;Cameron and Buddle 2017), will also differ from other major biomes on the planet. Therefore, the objective of this research was to document Arctic biodiversity patterns across multiple geographical scales, from within-site (sample to sample) to regional scales (i.e., across all of northern Canada), using ground-dwelling spiders (Araneae) as a model taxon, and to determine the relative importance of environmental and spatial drivers underlying spatial patterns of diversity in northern Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Three of the most notable long-term studies are yellow pitfall trapping at Zackenberg, northeast Greenland (Høye et al 2007;Høye and Forchhammer 2008;, the repeated Northern Insect Survey in Canada (Fernandez-Triana et al 2011;Ernst and Buddle 2015;Ernst et al 2016), and the spectacular long-term time series at Lake Myvatn in Iceland (Ives et al 2008). The monitoring program at Zackenberg is part of the Greenland Ecosystem Monitoring Program, nationally funded by Denmark.…”
Section: Arctic Long-term Monitoringmentioning
confidence: 99%
“…Although the Arctic contains fewer arthropod species per unit area than environments at lower latitudes, arthropod diversity is still high and makes up the largest component of multicellular biodiversity in the region (Hodkinson et al 2013;Høye and Sikes 2013;Ernst and Buddle 2015). Arthropods respond rapidly to environmental changes and are deeply entwined in Arctic food webs (Høye and Forchhammer 2008).…”
Section: Introductionmentioning
confidence: 99%